Tubulin-targeting antiparasitic herbicides : new insights into putative ligand-binding pockets and computational design of molecular equivalents - Flood, Christopher T. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2013)
Neglected diseases are a group of tropical infections which are especially endemic in lowincome populations in developing regions of Africa, Asia, and the Americas. Collectively these diseases affect more more than a biUion people worldwide. Malaria affects 300 million people and lolls 1-1.5 million people every year. One of the main causes for the comeback of malaria is that the most widely used drug against malaria, chloroquine, has been rendered useless by drug resistance in much of the world. New anti-malarial drugs are presently available but the potential emergence of resistance and their cost make it of utmost importance to continue searching for new drugs. Similarly, Trypanosoma brucei affects the people of 36 sub-Saharan countries with 300,000 new cases reported every year. The few drugs used for the treatment of the disease are either toxic, cause severe side effects or suffer from parasite resistance.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.